Leadership through the eyes of a public health professional: A journey of 43 years - Sanjiv Kumar (Wolters Kluwer Medknow Publications, 2020)
Leadership skills in a public health professional (PHP) are more important today in view of rapidly changing disease pattern, higher priority to universal health coverage, health in all policies, health being demanded as a human right, and emergence of pandemics from zoonotic diseases. Most of us become accidental leaders as we never receive training in leadership skills. This not only undermines the effectiveness of PHP but also undermines the credibility of public health as a specialty. Jim Collin's five levels of leadership are useful to understand the various levels of leadership for a PHP. Technical excellence which denotes first level of leadership is necessary but not sufficient to become a leader. One needs team work, emotional competencies, prioritization ( first things first), listening skills, advocacy, negotiation, networking skills, along with conviction, commitment, and courage to do what one thinks is right. Leadership is a life-long journey, not a destination. Being engaged in leadership for more than a decade, I developed a three domain leadership capacity development model very useful in designing and conducting leadership development trainings to develop leadership skills among PHPs, academicians, and health researchers.